Parliament Oversight on Local Government Financial Management an Empirical Evidence - Abdullah, Syukriy; Reza, Mirza Khairul; Junita, Afrah; Meutia, Tuti (Riset Akuntansi dan Keuangan Indonesia, 2020)
The purpose of this study is to explain the effect of the Political Background (PB) and Regulation Understanding (RU) on the Local Financial Oversight (LFO) by the Local House of Representatives (Dewan Perwakilan Rakyat Daerah/DPRD) of Pidie Regency, Aceh, moderated by Public Accountability (PA) and the Public Transparency (PT). Agency perspective is used to explain the phenomena and problems studied. Respondents in this study were 32 members of the DPRD involved in LFO and primary data obtained from questionnaires distributed to them. The model used is multiple linear regression with moderating. The results showed that PB had an effect on LFO, while the RU variable had no effect. Another finding is PT moderates the relationship PB with LFO.